The Influence of Poetry on Political News A Reading in the "Talibites' Assassinations" in the First Phase of the Abbasid Era - Essa AL-Masri (My University, 2011)
This study aims at conducting a critical reading to the poetry which accompanied historical political news in the book "Maqaatil AL_Talibiyyen" (Talibites' Assassinations) by Abu AL-faraj AL-Asfahani with special focus on the first abbasid phase in which there was a struggle between the Abbasids and their cousins, the Talibites. The study emanates from a notion that views the structure of poetry as a factor which may influence the structure of narrated news when the composer is deeply aware of the function of poetry and the particularity of its language and its considerable role in implying and signaling ideas or in directly stating them. The study consist of several sections which together deal with a single idea. It reviews the structure of news in ancient manuscripts of an additive style, it explains the nature of the correlation between the fictional and realistic structure in it, and uncovers the doctrinal political structure in "Maqatil AL-Talibiyyeen" in particular. Then it analyzes the verses that contained their news in the first phase and arranges them according to the poets, first in relation to the assassinated persons themselves, second in relation to their families and relatives, and third in relation to their supporter famous and mediocre poets.

يسعى هذا البحثُ إلى تقديم قراءة نقديَّة للشِّعر الذي رافق الأخبار التَّأريخيَّة ذات الطّابع السّياسيِّ في كتاب مقاتل الطّالبيّين لأبي الفرج الأصفهانيِّ، ويخصُّ بالقراءة الحقبة العبّاسيَّة الأولى التي دار الصِّراع فيها بين أولاد العمومة من الطّالبيّين والعبّاسيّين. وينطلقُ البحثُ في قراءته من فكرة ترى أنَّ بنية الشِّعر قد تؤثِّر في بنية الخبر المنثور؛ وذلك إذا كان المؤلِّفُ على وعيٍ عميقٍ بوظيفةِ الشِّعر، وبخصوصيَّة لغته، ودورها الكبير في الإيماء والإشارة إلى الأفكار، أو في التَّصريح بها والإرشادِ العلنيِّ إليها. وينتظمُ البحثَ محاورُ عدَّة تأتلف في مجموعها لمعالجة فكرةٍ واحدةٍ هي موضع الدَّرس، فيعرضُ لبنية الخبرِ مبيِّنًا تشكيلها وتركيبها في المصنَّفات القديمة ذات النَّسق التَّجميعيِّ، كما يُبيِّنُ طبيعة ائتلاف البنية الخياليَّة والواقعيَّة فيها، ويكشفُ عن البنية الاعتقاديَّة السّياسيَّة في كتاب مقاتل الطّالبيّين خاصَّة. ثمَّ يتناول بالتَّحليل الأشعار التي تضمَّنتها أخبارهم زمن العبَّاسيّين الأوَلِ، ويُرتِّبها وفق ناظمي الشِّعر من المقتولين أولاً، ثمَّ من أهلهم وذويهم ثانيًا، ثمَّ من الشُّعراء المشهورين والمغمورين من أنصارهم ثالثًا.
أثرُ الشِّعرِ في الخبَرِ السّياسيِّ قراءة في "مقاتل الطّالبيّين" زمن العبّاسيّين الأُوَلِ